Liquid organic matter from banana peel improves morpho-physiological traits of coffee seedlings - Soleh, Mochamad Arief; Zalfa, Inaz Nuzul; Ariyanti, Mira (Universitas Padjadjaran, 2023)
Due to its economic advantage, the Robusta coffee clones BP 308 and BP 939 are widely grown. Many factors affect coffee growth during the cultivation practice, especially in the availability of adequate nutrients at the nursery stages. Apart from inorganic fertilizer application, organic matter needs to be applied in the nursery stages to support plant growth, such as applying liquid organic matter (LOM) derived from banana peel waste. This study was conducted to find out how the LOM of banana peels affected the morphological and physiological responses of BP 308 and BP 939 clone Robusta coffee seedlings and what proper dosages of LOM were needed. The experiment was conducted at the Ciparanje Experimental Station, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor from January to April 2022. This experiment used a randomized block design method consisting of 10 treatments and 3 repetitions. The treatments tested included 1.5 g of NPK inorganic fertilizer; 10 mL.L-1.plant-1 LOM ; 20 mL.L-1.plant-1 LOM; 30 mL. L-1.plant-1 LOM and 40 mL. L-1 .plant-1 LOM that was given to both clones, namely BP 308 and BP 939. The results of this experiment showed that there were differences in the effect of LOM between BP308 and BP939 on the morphological response such as an increase in plant height and leaf number, on the physiological response such as chlorophyll index and stomatal conductance at the 3 months after treatment (MAT). The BP939 was partly better in response to LOM of 10 mL.L-1.plant-1on plant height, the BP308 was partly better in stomatal conductance.